Ethnobotany of Washim District (M.S.) India - Kshirsagar, Prachi; Bhogaonkar, P Y; Chavhan, Vinod; Dhole, Pankaj (Plantae Scientia, 2024)
Present paper documents 106 plant species belonging to 44 families used by rural and tribal people of Washim district. Eighty one species are used to treat human ailments – 56 species being used in monoherbal treatments while, 31 species are used in polyherbal formulations. Ten specis are used as veterinary medicine. Eighteen species are edible; while six are used for miscellaneous purposes.